(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article explores the study of phrasal verbs in the English language through a comparative analysis with Uzbek phraseological units and existing classifications. The author presents a structural and comparative classification of phrasal verbs and affixal verbs in both English and Uzbek, along with their comparative descriptions with other phraseological units. Additionally, the article examines key linguistic trends in the study of English phrasal verbs.